Operative management of anterior anus: Case report on single-center experience in a rural hospital - Nugraha, George Hagi; Azzahwa, Lyra Nayli; Puteri, Aulia Rahman; Putra, Galih Santoso (Indian Journal of Case Reports, 2025)
The anterior anus (AA) is a form of congenital anorectal malformation characterized by an anal position that is more anterior than the normal anatomical location, and is often associated with defecation disorders such as chronic constipation. We report the case of a 2-year-old girl who came with complaints of constipation since infancy, as well as the distance of the anus that seemed very close to the vagina. Clinical examination and anal position index calculations showed a value of 0.2, which confirmed the diagnosis of AA. Management is carried out through a reconstruction procedure without a colostomy. Post-operative evaluation showed significant improvements in the frequency and consistency of bowel movements. These results support the operative approach as the primary choice in cases of anterior anal with persistent functional complaints, in order to improve defecation function and improve the patient’s quality of life.